Modern family. The complete third season [videorecording (DVD)] - Levitan, Steven; O'Neill, Ed, 1946-; Burrell, Ty, 1967-; Vergara, Sofía, 1972-; Bowen, Julie (20th Century Fox Home Entertainment, 2012)
As the extended Pritchett/Dunphy clan faces an uproariously unpredictable array of family vacations, holiday hassles, troublesome in-laws, and surprising secrets, they still somehow manage to thrive together as one big, loving family even as they drive each other absolutely insane.